2012
DOI: 10.1089/gtmb.2011.0089
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Expanded Alleles of theFMR1Gene Among High-Risk Population in Indonesia by Using Blood Spot Screening

Abstract: The prevalence of Fragile X Syndrome (FXS) is 1 in 4000 in males and 1 in 2500 in males and females, respectively, in the general population. Several screening studies aimed at determining the prevalence of FXS have been conducted in individuals with intellectual disabilities (IDs) with a prevalence varying from 1.15% to 6.3% across different ethnic groups. A previous study in Indonesia showed an FXS prevalence of 1.9% among the ID population. A rapid, effective, and inexpensive method for FMR1 screening, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…A large portion of normal alleles with 3 AGG interruptions (8%), with the majority of these alleles having the 9-A-9-A-6-A-9 pattern (6.4% of patterns) was observed in Indonesia. The 9-A-9-A-6-A-9 pattern and CGG length of 36 repeats has been observed in previous studies to occur within Indonesian and Asian cohorts (30,38,39). Fifty AGG interruption patterns were observed in 277 FMR1 alleles genotyped from Mexico.…”
Section: Agg Interspersion Patterns By Countrysupporting
confidence: 58%
See 1 more Smart Citation
“…A large portion of normal alleles with 3 AGG interruptions (8%), with the majority of these alleles having the 9-A-9-A-6-A-9 pattern (6.4% of patterns) was observed in Indonesia. The 9-A-9-A-6-A-9 pattern and CGG length of 36 repeats has been observed in previous studies to occur within Indonesian and Asian cohorts (30,38,39). Fifty AGG interruption patterns were observed in 277 FMR1 alleles genotyped from Mexico.…”
Section: Agg Interspersion Patterns By Countrysupporting
confidence: 58%
“…These samples were previously screened to determine the prevalence rates of expanded alleles. Cohorts from Australia (n = 201) (28), Chile (n = 77), the United Arab Emirates (n = 263), Guatemala (n = 151) (29), Indonesia (n = 312) (30), Italy (n = 67), Mexico (n = 277), Spain (n = 358) (31), and the United States (n = 1,359) (32) were included. Individuals were recruited from the general population for the Italy, Spain, and United States samples.…”
Section: Participantsmentioning
confidence: 99%
“…(6,13) Another study conducted in 2012 by Winarni et al showed that the most common CGG repeat allele in an Indonesian high-risk population was 30 repeats, followed by 29 repeats, with a smaller percentage of 35 and 36 repeats. (11) Using sizing analysis, two out of five samples that were classified as expanded with respect to the 53-repeat reference control (TG-143 and TG-271) were determined to carry FM alleles of > 200 repeats, although the exact sizes of the FM expansions could not be determined by the kit. The remaining three samples that were classified as expanded (TG-153, TG-174 and TG-192) were false positives.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for FXS in high-risk populations such as those with ID is an effective means of identifying affected individuals and determining the prevalence of ID, and allow family members to undergo posttest genetic counselling sessions and cascade testing. (11) This study utilised a simple, quick and inexpensive method with high sensitivity and specificity for diagnosing FXS among institutionalised individuals with ID. (12)…”
Section: Introductionmentioning
confidence: 99%
“…Study populations have varied widely according to diagnostic categories of the subjects included. For example, an Indonesian study found a prevalence of 6 in 32 where there was a family history of FXS, but 1 in 144 in those with intellectual impairment alone [ 42 ]. A reported low prevalence of 1.1% from United States among children attending special education schools also included mentally retarded (12%), autism spectrum disorder (1%), learning disability (51%) and attention deficit hyperactivity disorder (35%) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%